Intergenerational Correlations of Extreme Right-Wing Party Preferences and Attitudes toward Immigration - Alexandra Avdeenko; Thomas Siedler (Institute for the Study of Labor (IZA), 2015)
This study analyzes the importance of parental socialization on the development of children's far right-wing preferences and attitudes towards immigration. Using longitudinal data from Germany, our intergenerational estimates suggest that the strongest and most important predictor for young people's right-wing extremism are parents' right-wing extremist attitudes. While intergenerational associations in attitudes towards immigration are equally high for sons and daughters, we find a positive intergenerational transmission of right-wing extremist party affinity for sons, but not for daughters. Compared to the intergenerational correlation of other party affinities, the high association between fathers' and sons' right-wing extremist attitudes is particularly striking.
Keywords: C23; D72; J62; P16; 330; political preferences; extremism; gender differences; longitudinal data; intergenerational links